Phenotypic and Genotypic Characterization of Tetracycline-Resistant Bacteria Isolated from Brantas River, Malang Raya and Their Biofilm Formation Ability: Phenotypic and Genotypic Characterization of Tetracycline-Resistant Bacteria - Mahira, Syarafin; Yoga Dwi Jatmiko; Maharani Pertiwi Koentjoro (Journal of Tropical Life Science, 2026)
Antibiotic resistance in aquatic environments has become an important public health concern due to the spread of antibiotic-resistant bacteria (ARB) through river water, which provides favorable conditions for biofilm formation and enables bacteria to survive environmental stresses, including antibiotic exposure. The Brantas River water is still widely used for household activities, increasing the potential dissemination of bacteria through water exposure. This study aims to determine the phenotypic characteristics, identify tetracycline-resistant bacterial species using 16S rRNA gene sequencing, and analyze the level of biofilm formation and cell density within the biofilm by tetracycline-resistant bacterial isolates. Tetracycline-resistant isolates were phenotypically characterized and identified using 16S rRNA gene sequencing. Detection of tetracycline resistance genes was performed by Polymerase Chain Reaction (PCR). Biofilm formation ability was evaluated using the crystal violet (CV) assay in Tryptic Soy Broth (TSB) and Brantas River water, exopolysaccharide (EPS) extraction, and then the cell density in the biofilm was calculated using Total Plate Count (TPC). Isolates TET-15.1 and TET-40.1 were found to be resistant to all four concentrations. Identification results showed similarities between TET-15.1 with Alcaligenes faecalis; and TET-40.1 with Serratia sp. The resistant genes found in both isolates were tet(S) and tet(B). Alcaligenes faecalis TET-15.1 had the highest biofilm formation ability and higher EPS production than Serratia sp. TET-40.1, with OD584 values ranging from 1.5 to 2.25 and EPS concentration of 4 – 5 mg/mL at tetracycline concentration of 8 μg/mL. The biofilm formation cycle reached maturity after 16 hours of incubation and then dispersed after 32 hours. These findings indicate that tetracycline-resistant bacteria from the Brantas River possess biofilm forming capabilities that may contribute to their environmental persistence and potential role in the dissemination of antibiotic resistance.